2017
DOI: 10.1136/bmjstel-2015-000070
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oral and video debriefing and its effect on knowledge acquisition following simulation-based learning

Abstract: IntroductionLearning from simulation takes place to a large extent in debriefing; however, there is still sparse knowledge about the advantages and disadvantages of debriefing methods. 2 common forms are video-assisted and oral only debriefing. We set out to determine if there is increased knowledge acquisition for candidates undergoing video, rather than oral debriefing.MethodsSecond year doctors were randomised to a training day with oral or video feedback. Candidates underwent an emergency clinical scenario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…The recordings enabled asking specific and very detailed questions such as ‘ What is he doing here in the background ?’ which would have been difficult or impossible without the video. Research on video debriefing has so far not very convincingly shown beneficial effects in comparison with non-video debriefing 3 5 11–13 38 39. This study makes a contribution to our understanding about how, and during which phases, it may be worthwhile structuring discussions around the video.…”
Section: Discussionmentioning
confidence: 82%
“…The recordings enabled asking specific and very detailed questions such as ‘ What is he doing here in the background ?’ which would have been difficult or impossible without the video. Research on video debriefing has so far not very convincingly shown beneficial effects in comparison with non-video debriefing 3 5 11–13 38 39. This study makes a contribution to our understanding about how, and during which phases, it may be worthwhile structuring discussions around the video.…”
Section: Discussionmentioning
confidence: 82%
“…El docente debe estar presto a aprender durante el transcurso del debriefing; las cargas cognitivas que puede presentar son muchas, sin embargo la preparación del debriefing y la experiencia podría mitigar dichas cargas, la utilización de un co debriefing también apoya a disminuir estas cargas cognitivas; es importante el manejo de estas cargas cognitivas para https://culturacuidados.ua.es poder seguir los objetivos de aprendizaje propuestos (Cheng et al, 2015;Coggins et al, 2020;Couper et al, 2013;Farooq et al, 2017;Fraser et al, 2018).…”
Section: Resultsunclassified
“…The practical applications today are to provide educators with visualizations of existing metrics after the simulated case to use during debriefing. For example, learners may watch their parts of the recorded simulation, including the metrics, which may increase learning ( Farooq et al, 2017 ; Gordon et al, 2017 ). Recording expert teams performing challenging teamwork tasks may be used in teamwork training to set masterly learning goals and provide specific guidance during rapid cycle deliberate practice ( Barsuk et al, 2016 ; Salvetti et al, 2019 ; Ng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%